The association between blood pressure variability and perihematomal edema after spontaneous intracerebral hemorrhage - Sondag, Lotte; Wolsink, Axel; Jolink, Wilmar M. T.; Voigt, Sabine; van Walderveen, Marianne A. A.; Wermer, Marieke J. H.; Klijn, Catharina J. M.; Schreuder, Floris H. B. M. (Frontiers in Neurology, 2023)
Background Perihematomal edema (PHE) after spontaneous intracerebral hemorrhage (sICH) is associated with clinical deterioration, but the etiology of PHE development is only partly understood. Aims We aimed to investigate the association between systemic blood pressure (BP) variability (BPV) and formation of PHE. Methods From a multicenter prospective observational study, we selected patients with sICH who underwent 3T brain MRI within 21 days after sICH, and had at least 5 BP measurements available in the first week after sICH. Primary outcome was the association between coefficient of variation (CV) of systolic BP (SBP) and edema extension distance (EED) using multivariable linear regression, adjusting for age, sex, ICH volume and timing of the MRI. In addition, we investigated the associations of mean SBP, mean arterial pressure (MAP), their CVs with EED and absolute and relative PHE volume. Results We included 92 patients (mean age 64 years; 74% men; median ICH volume 16.8 mL (IQR 6.6–36.0), median PHE volume 22.5 mL (IQR 10.2–41.4). Median time between symptom onset and MRI was 6 days (IQR 4–11), median number of BP measurements was 25 (IQR 18–30). Log-transformed CV of SBP was not associated with EED (B = 0.050, 95%-CI −0.186 to 0.286, p = 0.673). Furthermore, we found no association between mean SBP, mean and CV of MAP and EED, nor between mean SBP, mean MAP or their CVs and absolute or relative PHE. Discussion Our results do not support a contributing role for BPV on PHE, suggesting mechanisms other than hydrostatic pressure such as inflammatory processes, may play a more important role.